Infective Uvulitis in a Child. Issue 2 (February 2022) - De Pieri, Carlo; Valentini, Elena; Pusiol, Anna; Passone, Eva; Gamalero, Lisa; Cogo, Paola Elisa
Abstract : Abstract: Infective uvulitis is a rare condition in children. In this report, we describe the case of a 4-year old-patient who presented a group A Streptococcus pharyngitis with uvulitis. No signs of epiglottitis were detected at nasal fibroscopy. She recovered rapidly with intravenous antibiotic therapy and 2 days of corticosteroid. Uvulitis is usually caused by group A Streptococcus or Haemophilus influentiae, but also other bacteria can be detected. Uvulitis can be isolated, or it can occur with epiglottitis and become an emergency.